An innovative hippocampal-sparing whole-brain radiotherapy planning approach via the Halcyon system: achieving lower hippocampal doses - Tang, Ran; Lan, Maoying; Sun, Xingru; Luo, Yue; Gu, Anyan; Liu, Qing; Li, Yingjing; Yang, Guozi; Pan, Zhenyu; Deng, Guanhua (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the feasibility and dosimetric benefits of Halcyon-based coplanar dual-arc volumetric modulated arc therapy (VMAT) for hippocampal-avoidance whole brain radiotherapy (HA-WBRT).MethodsTwenty-one HA-WBRT patients were replanned using dual-arc VMAT (collimator 23°/293°) on Halcyon and Truebeam. The planning target volume (PTV) was segmented into three substructures and optimized with different weight parameters. Dosimetric parameters of PTV, monitor units (MUs), does to organs-at-risk(OARs), hippocampal normal tissue complication probability (NTCP) and gamma passing rate were recorded.ResultsAll plans met RTOG 0933 criteria. The Halcyon plans demonstrated significantly better homogeneity index (HI) and V30Gy of the PTV (HI: 0.105 vs. 0.121, P<0.001; V30Gy: 97.1% vs. 96.3%, P<0.001), alongside reduced hippocampal dose (D100%: 626.8 vs. 695.0cGy; Dmean: 850.0 vs. 898.4cGy; Dmax: 1348.1 vs. 1399.8 cGy; NTCP: 34.16% vs. 31.67%, P ≤ 0.001), OARs sparing improved for Lens Dmax (495.0 vs. 525.8cGy, P = 0.001), Optic nerves Dmax(3047.7 vs. 3077.6cGy, P = 0.006), and eyes Dmean(927.1 vs. 937.9cGy, P = 0.009). The average gamma passing rates were higher for Halcyon than Truebeam (3%/2mm: 99.96% vs. 99.85; 2%/2mm: 99.83% vs. 99.49%).ConclusionsUnder the innovative planning approach, redefined hippocampal-sparing radiotherapy using Halcyon system, providing superior prescription dose coverage, improved OAR sparing, and reduced hippocampal NTCP.